Pro-inflammatory cytokines and their epistatic interactions in genetic susceptibility to schizophrenia - Srinivas, Lekshmy (J Neuroinflammation, 2016)
BACKGROUND: In schizophrenia, genetic background may provide a substrate for intrinsic maldevelopment of the brain through environmental influences, by recruiting neurotrophic factors and cytokines, to trigger the changes that lead to impaired neuronal functions. Cytokines being the key regulators of immune/inflammatory reactions are also known to influence the dopaminergic, noradrenergic, and serotonergic neurotransmission. Therefore, functional polymorphisms in cytokine genes may result in imbalances in the pro- and anti-inflammatory cytokine production. METHODS: We screened polymorphisms in pro- and anti-inflammatory cytokine genes using a case-control association study in a South Indian population. The role of allele, genotype, haplotype, and diplotypes of these cytokine genes and their epistatic interactions were assessed in contributing to the risk of developing schizophrenia. Meta-analysis for the reported associations was also monitored for global significance. RESULTS: The pro-inflammatory cytokine gene polymorphisms in IL1Ars1800587, IL6rs1800796, TNFArs361525, and IFNGrs2069718 were associated with schizophrenia. The study also provides significant evidence for strong epistatic interactions among pro-inflammatory cytokine genes IL6 and IFNG in the development of schizophrenia. In silico analysis suggested that associated risk variants were indicative of altered transcriptional activity with higher production of IL1α, IL-6, TNF-α, and IFN-ɤ cytokines. Meta-analysis indicated heterogeneity among study population while IL1Ars1800587 was found to be globally significant. CONCLUSIONS: It is important to identify the nature of inflammatory response that can be amplified by the environment, to influence either Th1 response or Th2 response. The associated functional variants in the study are involved with increased expression resulting in higher production of the pro-inflammatory cytokines IL-1α, IL-6, TNF-α, and IFN-γ. The interaction of immunological stressors with these high producer alleles of pro-inflammatory cytokines may suggest that even a lower threshold may be sufficient to induce a resultant chronic effect on the psycho-social and environmental stressors that may result in the development and pathogenesis of schizophrenia. Understanding environmental factors that influence the expression of these pro-inflammatory cytokine genes or their interaction can possibly help in dissecting the phenotypic variation and therapeutic response to antipsychotics in schizophrenia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-016-0569-8) contains supplementary material, which is available to authorized users.